2016
DOI: 10.1021/acs.est.6b01422
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Climate and Sewer Condition on Virus Transport to Groundwater

Abstract: Pathogen contamination from leaky sanitary sewers poses a threat to groundwater quality in urban areas, yet the spatial and temporal dimensions of this contamination are not well understood. In this study, 16 monitoring wells and six municipal wells were repeatedly sampled for human enteric viruses. Viruses were detected infrequently, in 17 of 455 samples, compared to previous sampling at these wells. Thirteen of the 22 wells sampled were virus-positive at least once. While the highest virus concentrations occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…The reasons for this are uncertain, but could be linked to more intense rainfall and/or flooding under wetter conditions (Bridgman et al 1995, Wu et al 2016 and the activation of rapid recharge pathways and/or shallower groundwater tables under wetter climate conditions (Gotkowitz et al 2016, Cuthbert et al 2019. It has been previously suggested that under wetter climatic conditions, microbiological contamination may be higher (Gotkowitz et al 2016), and with higher contamination during the wet season (e.g. Sorensen et al 2015aSorensen et al , 2015b.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this are uncertain, but could be linked to more intense rainfall and/or flooding under wetter conditions (Bridgman et al 1995, Wu et al 2016 and the activation of rapid recharge pathways and/or shallower groundwater tables under wetter climate conditions (Gotkowitz et al 2016, Cuthbert et al 2019. It has been previously suggested that under wetter climatic conditions, microbiological contamination may be higher (Gotkowitz et al 2016), and with higher contamination during the wet season (e.g. Sorensen et al 2015aSorensen et al , 2015b.…”
Section: Discussionmentioning
confidence: 99%
“…This leaking sewage can infiltrate drinking water distribution pipes under conditions of low water pressure or when there is a water main break [ 61 ]. Sewage can also contaminate groundwater that is used as a drinking water source, which is of high concern [ 18 , 19 , 59 , 62 ], particularly if it is untreated [ 63 ]. Drinking water systems, along with wastewater and sewer conveyance infrastructure, are ranked as a D− and D, respectively, by the American Association of Civil Engineers [ 64 ], and can be expected to deteriorate further over time without significant investments.…”
Section: Discussionmentioning
confidence: 99%
“…Human fecal contamination, i.e., untreated sewage, has the highest potential to cause disease because humans are the reservoirs for many human pathogens [ 17 ], although agricultural runoff can also carry zoonotic pathogens [ 10 ]. In urban areas, untreated sewage released from failing sewer infrastructure can leach into soil and migrate into groundwater [ 18 , 19 ] and into drinking water distribution systems under conditions of reduced pressure [ 20 ]. Stormwater systems have been found to be frequently contaminated by sanitary sewage as a result of infiltration of leaking sewage or illicit cross-connections, resulting in untreated sewage discharging directly into rivers and streams [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It constitutes about 95% of the world’s accessible freshwater (Chilton and Seiler 2006 ; Howard et al 2006 ; McKay 2011 ) and is often used with little or no treatment (Pedley et al 2006 ). Contamination of groundwater with human enteric viruses is a global issue (Blaschke et al 2016 ; Gotkowitz et al 2016 ; Hynds et al 2014 ; USEPA 2006a , b ), as consumption of contaminated water can result in elevated rates of endemic illness and waterborne disease outbreaks in affected communities (Beer et al 2015 ; Borchardt et al 2011 ; Cho et al 2014 ; Guzman-Herrador et al 2015 ; Hilborn et al 2013 ; Jack et al 2013 ; Wallender et al 2014 ; Zhou et al 2012 ). Enteric viruses implicated in waterborne outbreaks include enteroviruses, hepatitis A, rotavirus, and norovirus (Craun et al 2010 ; Hejkal et al 1982 ), but others such as adenoviruses, Aichi virus 1, hepatitis E, and reoviruses, potentially are capable of groundwater-borne transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Viral and other pathogens and microbial indicators enter aquifers through multiple sources and pathways, including leachates from sanitary landfills, on-site septic waste treatment discharges, broken sewage lines, runoff from urban, agricultural and natural areas, and water reuse by direct injection of inadequately treated wastewater into aquifers (Borchardt et al 2012 ; Costan-Longares et al 2008 ; Gotkowitz et al 2016 ). Fecal contamination from the surface may also get into groundwater through improperly constructed, protected, or maintained wells (Hynds et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%